Antioxidative activity and phytochemical composition of dried apricot - Erden, Yavuz; Bircan, Burak; Yılmaz, Ökkeş; Erecevit, Pınar (My University, 2013)
In this study, the phytosterol and vitamin values of apricot fruits, which had been dried with different methods, and the antioxidant activity against iron (II) chloride (FeCl2) and hydrogen peroxide (H2O2) induced in vitro hepatitis oxidation have been determined. In addition, antioxidant capacity of apricots was determined by using DPPH free radical. As a result, apricot extracts inhibited lipid peroxidation and protected amount of total protein. Additionally, DPPH free radical scavenging effect of the species showed a parallel increase in dose. We think that rich phytochemical compounds of apricot fruits (for example; phytosterols, flavonoids, polyphenols and vitamins) play a role in this effect.

Bu çalışmada, farklı yöntemlerle kurutulmuş kayısı meyvesinin fitosterol ve vitamin seviyeleriyle, demir (II) klorür ve hidrojen peroksitle indüklenen in vitro karaciğer oksidasyonuna karşı antioksidan aktivitesi belirlendi. Ayrıca kayısının antioksidan kapasitesi DPPH serbest radikali kullanılarak belirlendi. Sonuçta, kayısı ekstraktları lipid peroksidasyonunu önledi ve total protein miktarını korudu. Buna ek olarak, türlerin artan doza paralel olarak DPPH serbest radikali temizleme etkisi görüldü. Biz bu etkinin kayısı meyvesindeki zengin fitokimyasal kompozisyonun (örneğin; fitosteroller, flavonoidler, polifenoller ve vitaminler) rol oynadığını düşünüyoruz
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Apricot; Lipid peroxidation; Protein; DPPH; Vitamin; Phytosterol; Kayısı; Lipid peroksidasyonu; Fitosterol